Tests for Anxiety‐Related Behavior in Mice. Issue 4 (2nd December 2015) - Hölter, Sabine M.; Einicke, Jan; Sperling, Bettina; Zimprich, Annemarie; Garrett, Lillian; Fuchs, Helmut; Gailus‐Durner, Valerie; Hrabé de Angelis, Martin; Wurst, Wolfgang
Abstract : Phenotyping of inbred mouse strains and genetically modified mouse models for characteristics related to neuropsychiatric diseases includes assessing their anxiety‐related behavior. A variety of tests have been developed to measure anxiety in laboratory rodents and these tests have been placed under scrutiny over the years concerning their validity. Here we describe the most widely used tests for anxiety in mice. The protocols we present are established methods used in the German Mouse Clinic (GMC), with which alterations in anxiety could successfully be discovered in mouse mutants. Moreover, since baseline anxiety levels in mice are easily influenced by a great variety of disturbances, we carefully outline the critical parameters that need to be considered. © 2015 by John Wiley & Sons, Inc.